A photosynthetic–respiratory electron transport chain chimera based on photosystem I and cytochrome c oxidase on graphene oxide - Xiaoping Zhu; Matthew J. Kummer; Carolyn E. Lubner; Vasily Kurashov; William Carr; John H. Golbeck; Robert A. Niederman; Lev G. Mourokh; Shelley D. Minteer; Paul G. Falkowski; Michele Vittadello (Proceedings of the National Academy of Sciences, 2026)
The self-assembly of enzyme proteins on 2D nanomaterials has enabled the construction and functional control of viable biochemical pathways. However, enzymatic cascades, which combine essential components of the photosynthetic and respiratory electron transport chains in tandem, have thus-far remained elusive. Herein, we have investigated a galvanic biohybrid nanosystem coupling photosystem I and cytochrome c oxidase on the surface of graphene oxide nanosheets in colloidal suspension. The oriented immobilization of the enzymes was facilitated by Ni-coordination sites tethered to the carbon basal plane, with negligible parasitic O 2 consumption. Transient absorption and electrochemical measurements provided evidence of electron transfer between donors and acceptors, leading to light-induced O 2 consumption of up to 70 out of 120 O 2 molecules/s/CcO unit. Graphene oxide behaves as an electronic reservoir and as an electroactive support, enabling electron transport, in concert with cytochrome c , as well as small-molecule redox mediators and reductants. This study provides a state-of-the-art approach for the exploration of photoelectron transfer in membrane-free suspensions of nanosurface-anchored photosynthetic–respiratory enzymatic chains.